Global Leisure and the Struggle for a Better World (Leisure Studies in a Global Era, 2018)
This edited collection highlights the diversity and reach of global leisure studies and global leisure theory. It explores the impact of globalization on leisure, and the sites of resistance and accommodation found in local, virtual and global leisure spaces. Unlike any other collection on leisure studies, Global Leisure and the Struggle for a Better World is truly representative of the diversity of the large and growing leisure scholarship across the globe. It demonstrates how researchers in leisure studies and sociology of leisure are applying complex theory to their work, and how a new theory of global leisure is emerging.